The role of the Foreign Direct Investment inflows on export in Azerbaijan: An ARDL approach - Calal, Maharram Huseynov; Ilham, Karimov Mehman; Vaqif, Nesirov Elcin; Calal, Zeynalli Elay; Mardan, Tahirova Gulchin (Universitas Islam Indonesia, 2023)
Purpose ― This study aims to investigate the impact of FDI inflows on Trade in Azerbaijan from 1993 to 2021. Method ― This study uses the datasets from the World Bank Database. It employs the Augmented Dickey and Fuller (ADF), Phillips and Perron (PP), Zivot and Andrews (ZA), ARDL bounds testing approach, and the Granger Causality tests for the empirical part of the study.Findings ― The bound test shows the presence of cointegration between FDI and Export. The estimated long-run equation suggests a positive and significant relationship, whereas the estimated short-run equation indicates a positive but insignificant relationship between FDI and export. Additionally, the results of Granger causality test show a unidirectional causality running from FDI to export. Implications ― Since the FDI inflows show a positive effect on the export of Azerbaijan, most foreign investments come into the oil and gas sector. Accordingly, oil and gas products and services account for a significant share of exports in Azerbaijan. Policymakers might need new regulations to attract more attention from foreign investors to non-oil sectors.Originality/value ― There were vast studies about FDI and trade relationships in different countries with different techniques. This study is unique because it employs a new methodology and the latest dataset in which Azerbaijan was a focused area for the first time.